2008
DOI: 10.4315/0362-028x-71.12.2460
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Listeria monocytogenes in Raw Fruits by Enterocin AS-48

Abstract: The purpose of this study was to determine the effect of enterocin AS-48 on Listeria monocytogenes CECT 4032 in fruits and fruit juice. Fruits were contaminated with a L. monocytogenes cell suspension, washed with enterocin AS-48 (25 microg/ml) or with sterile distilled water as control, and stored at different temperatures (-20, 6, 15, 22 degrees C). Washing treatments significantly inhibited or completely inactivated L. monocytogenes in strawberries, raspberries, and blackberries stored at 15 and 22 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 42 publications
0
22
0
4
Order By: Relevance
“…Further experiments carried out in fruits and fruit juices have shown that the anti-listeria effect of AS-48 (25 lg ml À1 ) depended on the fruit type and was much more effective in juices, probably due to the more homogeneous distribution of the enterocin in the liquid food matrix. In this case AS-48 showed also to be in general more effective at low temperatures (6-20°C) (Cobo Molinos et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
“…Further experiments carried out in fruits and fruit juices have shown that the anti-listeria effect of AS-48 (25 lg ml À1 ) depended on the fruit type and was much more effective in juices, probably due to the more homogeneous distribution of the enterocin in the liquid food matrix. In this case AS-48 showed also to be in general more effective at low temperatures (6-20°C) (Cobo Molinos et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
“…Although the listeriosis outbreak evaluated here is the first to be attributed to whole caramel apples, studies have shown that L. monocytogenes is capable of both surviving and growing on raw fruits such as whole and cut melons (13,14,20,23,27), melon pulp (26), cut pears (1,11,23), and whole and cut berries (1,23). This pathogen also can proliferate on fresh-cut apple slices when contamination occurs after processing procedures, such as peeling and cutting (2, 4, 12).…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that L. monocytogenes can grow in a number of vegetables [32][33][34], in non-acidic fruits [35,36] and in acidic fruits such as tomatoes [37], peeled Hamlin oranges [38], sliced raspberries, pear or kiwi [36], and in Golden Delicious apple slices [39,40]. In 2014, a listeriosis outbreak occurring in the USA was linked to commercially-produced, prepackaged whole caramel apples [4].…”
Section: Discussionmentioning
confidence: 99%